(untitled) (Bangladesh Journal of Psychiatry, 2018)
Mass psychogenic illness is not new in Bangladesh but in the year 2007, the sudden outbreak all over Bangladesh created a panic nationwide. The objective of the study was to investigate sociodemographic and other variables attributed to the disease. The first outbreak of this illness took place in Adiabad Islamia High School and College, Raipura, Narsinghdi. We rationally decided to conduct our research in this school in case-control design. Within 12 months’ study period, 125 students of class VI to X (45 cases and 80 controls) were interviewed face-to-face by structured questionnaire containing separate questionnaire for students and guardians. The result of the study showed that, all the cases came from lower socioeconomic class, majority (71.1%) from 14 to 16 years age group and most (77.8%) of the cases were female. Outbreak rapidly spread among the cases mostly by smelling foul odor (40%) and seeing index cases (33.3%). Majority (51.2%) of the cases and controls thought that the illness was due to both physical and psychological causes though most of them (93.6%) did not hear about the disease previously. It was evident that the role of socio-demographic variables for attributing the symptoms pattern of the disease was ambiguous. However early recognition of psychological stressors and prompt exclusion of physical illness can prevent the occurrence and rapid spread of the disease. Bang J Psychiatry June 2016; 30(1): 14-19